Characterization of the Adsorption Mechanism of Cadmium(II) and Methylene Blue upon Corncobs Activated Carbon. (11th February 2023) - Gundogdu, Ali; Bozbeyoglu, Pinar; Imamoglu, Mustafa; Baltaci, Cemalettin; Duran, Celal; Bulut, Volkan N.
Abstract: A promising new activated carbon (AC) was produced from corncobs (CCs) by boric acid-based chemical activation to remove methylene blue (MB) as an organic pollutant and cadmium ions (Cd 2+ ) as an inorganic pollutant from aqueous solutions. After the produced activated carbon (CCs-AC) was characterized, the adsorption mechanism of CCs-AC, which is one of the most interesting topics in the literature, was the primarily focus. The possible adsorption mechanisms of Cd 2+ and MB on CCs-AC from aqueous solutions are discussed with respect to pH, thermodynamic values, and regeneration parameters. The results show that the adsorption of Cd 2+ on CCs-AC was favorable at pH values higher than 4. In contrast, the adsorption process was almost pH-independent for MB. Variation of pH showed that the adsorption of Cd 2+ on CCs-AC primarily occurs by electrostatic interaction. However, MB adsorption may also involve π-π dispersion forces and partial hydrogen bonding. The Cd 2+ adsorbed on CCs-AC was quantitatively desorbed by HCl, whereas MB was not desorbed quantitatively by any solution. While a temperature increase has a positive effect on the adsorption of both methylene blue and Cd 2+, the thermodynamic results show that MB adsorption is primarily chemisorption (Δ H of 24.28 kJ/mole), while Cd 2+ adsorption is mostly physisorption (Δ H of 7.20 kJ/mole). Using Langmuir adsorption isotherms, the MB adsorption capacity of CCs-AC, which primarily has a microporous structure, was 0.88 mmol/g, while the Cd 2+ adsorption capacity was 1.28 mmol/g.